Bimbingan Teknis Pendataan Massal Wajib Pajak Daerah Kabupaten Tegal Berbasis Nomor Induk Kependudukan Bagi Perangkat Desa Kecamatan Jatinegara Kabupaten Tegal - Amin, Mohammad Arridho Nur; Wahyudi, Catur; Muttaqin, Ibnu; Amirah; Murdiati, Sri; Sulistyani, Tri; Herwinarni, Yuniarti; Amalia, Mei Rani (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
The Tegal Regency mass taxpayer data collection program based on population identification numbers for Jatinegara sub-district village officials is a program carried out by the Tegal Regency regional government to collect data on how many tax objects are owned by residents in each sub-district. This program was carried out with the aim of providing the government with data that would later be used to calculate how much tax would be paid by taxpayers in each village. Keep in mind that taxes are one of the largest revenues for local governments. In Jatinegara sub-district, the amount of data that has been input and verified is 80% greater than in the other 6 sub-districts. This is because the village operator in charge of input can be committed to making the program a success.